2019
DOI: 10.1111/1365-2656.12996
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the ecological impacts of an alien invader: Experimental approaches reveal the trophic consequences of competition

Abstract: Ecological theory on the trophic impacts of invasive fauna on native competitors is equivocal. Whilst increased interspecific competition can result in coexisting species having constricted and diverged trophic niches, the competing species might instead increase their niche sizes to maintain energy intakes. Empirical experiments can test invasion theory on competitive interactions and niche sizes across different spatial scales and complexity. The consequences of increased interspecific competition from a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 59 publications
0
16
2
Order By: Relevance
“…Indeed, the highest fish density was in TL i , in large part caused by the high density of the Arno goby P. nigricans (Table S2), an invertivore (Pompei et al 2014 ). However, experimental studies have shown decreased trophic niche sizes in relation to interspecific competition in B. barbus and other cyprinids (Britton et al 2019 ; De Santis et al 2021 ), which contrasts with the findings of this study. Specialization and subsequent reduction in trophic niche breadth have also facilitated the coexistence between other omnivorous fishes when resources are limited (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, the highest fish density was in TL i , in large part caused by the high density of the Arno goby P. nigricans (Table S2), an invertivore (Pompei et al 2014 ). However, experimental studies have shown decreased trophic niche sizes in relation to interspecific competition in B. barbus and other cyprinids (Britton et al 2019 ; De Santis et al 2021 ), which contrasts with the findings of this study. Specialization and subsequent reduction in trophic niche breadth have also facilitated the coexistence between other omnivorous fishes when resources are limited (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Invasive alien species (IAS) are nowadays recognized as a major component of the global decline in biodiversity. Great efforts have been spent to find general patterns able to predict the invasiveness, introduction paths, and impacts [1][2][3][4][5][6], with the aim to better allocate resources toward the management of the most problematic IAS [7]. Nevertheless, the impacts of biological invasions are highly context-dependent [8][9][10], triggering the predictions of the consequences of successful invasions [11].…”
Section: Introductionmentioning
confidence: 99%
“…trophic niche size and position) of a model species is altered by the increased abundance of a co‐existing species, and how these impacts relate to those from increased intra‐specific competition. The model animals were freshwater fishes, as these are adaptable and tractable animals that provide excellent model systems for experimental competitive studies with, for example, their indeterminate nature of growth enabling correlation with competitive success (Britton et al., 2019; Ward et al., 2006). The model species was chub Squalius cephalus , a fish of the Cyprinidae family that is found throughout much of north‐west Europe.…”
Section: Introductionmentioning
confidence: 99%